Workplace Violence against Clinical Workers in Tabriz Educational Hospitals - Sahebi L; Gholamzadeh Nikkjoo R (نشریه پرستاری ایران, 2011)
Background & Aims: Workplace violence is one of the most complex and dangerous occupational hazards facing nurses working in today's health care environment and it has been noted that workplace violence most frequently occurs in hospitals .The purpose of this study was to assess the situation of workplace violence committed against healthcare workers in Tabriz.   Materials & Methods : It was a descriptive, cross- sectional study. Clinical personel (n 400) of Tabriz educational hospitals (%13 of study population) were recruited by cluster sampling of hospitals, and randomly selection of one cluster in each group (seven hospitals were selected) considering their position. Data was collected using a questionnaire through face- to- face interviews and analyzed by logistic regression using SPSS-PC (v.16).   Results : Twenty-one percent and 64.3 percent of workers reported experiencing physical and verbal workplace violence during the last year respectively. The frequency of reported violence was %23.6. There was a strong correlation between physical and verbal violence (p<0.001).Avoidance of reporting violence was occurred because of shrug violence off (%31.9) or to be known as an offending or problematic person (%18.9). Men had more chance to confront with violence than women (CI: 0.26-0.82, p<0.009). Conclusion: Performing some measures such as educational courses about prevention of violence, repression of the opponent’s anger explanation of rules and regulations for workers and clients are recommended.